Investigating the impact of distinct contemplative mental trainings on daily life stress, thoughts and affect—Evidence from a nine-month longitudinal ecological momentary assessment study. (August 2022) - Linz, R.; Puhlmann, L.M.C.; Engert, V.; Singer, T.
Abstract: Mindfulness-based mental training interventions have become a popular means to alleviate stress and stress-associated health risks. Previous scientific investigations emphasize the importance of exploring the effects of such interventions in naturalistic settings to evaluate their implementation into daily life. Therefore, the current study examined the effects of three distinct mental training modules on a range of measures of daily life experience in the scope of the ReSource Project, a 9-month longitudinal mental training study comparing modules targeting attention and interoception (Presence), socio-affective (Affect) or socio-cognitive abilities (Perspective). We used ecological momentary assessment (EMA) to repeatedly probe levels of stress and stress-coping efficacy combined with stress-reactive cortisol levels, and further explored arousal, affective states, and thought patterns in the daily lives of 289 healthy adults (172 women; 20–55 years). We found increased presence-focused thought and heightened arousal after a training duration of 3–6 months, independent of the type of prior training. Increased coping efficacy emerged specifically after socio-cognitive Perspective training, following 6–9 months of training duration. No training effects were found for subjective stress, stress-reactive cortisol levels, or daily life affect. Our findings corroborate and add ecological validity to previous ReSource findings by showing that they replicate in participants' everyday environment. Regarding endocrine and subjective stress markers, our results suggest caution in generalizing acute laboratory findings to individuals' everyday routines. Overall, the current study provides substantiated insights into how cultivating one's mind through contemplative mental training translates to daily life experience, enhances stress-coping, and may ultimately aide in maintaining health. Highlights: EMA of subjective (stress) experience and cortisol levels over 9 months. Effects of distinct meditation-based mental training modules are investigated. Stress-coping is enhanced specifically after training socio-cognitive capabilities. Increased present-moment focus in daily life thinking after 3 months of practice.